miR-221 affects multiple cancer pathways by modulating the level of hundreds messenger RNAs - Lupini, Laura; Bassi, Cristian; Ferracin, Manuela; Bartonicek, Nenad; D'Abundo, Lucilla; Zagatti, Barbara; Callegari, Elisa; Musa, Gentian; Moshiri, Farzaneh; Gramantieri, Laura; Corrales, Fernando J.; Enright, Anton J.; et al. (Frontiers in Genetics, 2013)
microRNA miR-221 is frequently over-expressed in a variety of human neoplasms. Aim of this study was to identify new miR-221 gene targets to improve our understanding on the molecular tumor-promoting mechanisms affected by miR-221. Gene expression profiling of miR-221-transfected-SNU-398 cells was analyzed by the Sylamer algorithm to verify the enrichment of miR-221 targets among down-modulated genes. This analysis revealed that enforced expression of miR-221 in SNU-398 cells caused the down-regulation of 602 mRNAs carrying sequences homologous to miR-221 seed sequence within their 3’UTRs. Pathways analysis performed on these genes revealed their prominent involvement in cell proliferation and apoptosis. Activation of E2F, MYC, NFkB and β-catenin pathways was experimentally proven. Some of the new miR-221 target genes, including RB1, WEE1 (cell cycle inhibitors), APAF1 (pro-apoptotic), ANXA1, CTCF (transcriptional repressor), were individually validated as miR-221 targets in SNU-398, HepG2 and HEK293 cell lines. By identifying a large set of miR-221 gene targets, this study improves our knowledge about miR-221 molecular mechanisms involved in tumorigenesis. The modulation of mRNA level of 602 genes confirms the ability of miR-221 to promote cancer by affecting multiple oncogenic pathways.